The Impact of an Organization Development Intervention on the Strength-Based Leadership Behaviors of Team Leaders and Team Members: A case study in the Health Systems Division of Philips Thailand - Ruethaivanich, Kampon; Scott, Ph.D., Arlene (ABAC ODI JOURNAL Vision. Action. Outcome, 2017)
Abstract This study was designed to determine the impact of the organization development interventions on strength-based leadership behaviors of team leaders in order to support the strategic objectives of an organization in developing a capable workforce, winning in the market, and creating an ability to capture rising opportunities associated with the aging population trend in Thailand. The theoretical framework of leadership for this action research project use the five leadership practices of Kouzes and Posner: challenging the process, inspiring a shared vision, enabling others to act, modeling the way, and encouraging the heart. These five practices are regarded as strength-based leadership behaviors and share similar characteristics with culture competencies of the focal organization in this study. Both quantitative and qualitative methods were conducted. The research instruments were the Leadership Practices Inventory (LPI) and the structured-interview. Quantitative data was used to examine the change in level of the team leaders’ strength-based leadership behaviors and qualitative data was used to examine the impact of the team leader’s strength-based leadership behaviors on their team members. Two statistical tools (arithmetic mean and paired sample t-test) were utilized in this study. The data collected confirmed that after the organization development interventions, there was a change in the level of the strength-based leadership behaviors of team leaders. It also reflected that these changes resulted in an impact on their team members. This research has responded to the focal organization’s need of developing leadership skills within its workforce. While findings supported the research objectives and proved the hypotheses, the organization also strives for sustainable behavioral change, which will require further action. This next step will help create truly effective team leaders who can make a greater impact in the long run. Keywords: strength-based leadership behaviors, effective leader, organization development intervention, change, impact of leadership behaviors